Let $z_i$ be complex numbers such that $|z_i| = 1$ .

Prove that :

$$ z\, :=\, \frac{z_1+z_2+z_3 +z_1z_2+z_2z_3+z_1z_3}{1+z_1z_2z_3} \in \mathbb{R} $$

This problem was featured on my son's final exam today, I tried helping him with this, but I guess I got a bit rusty myself.

Any ideas ?

  • 4
    $\begingroup$ Multiply with $$\frac{\overline{z}_1\cdot \overline{z}_2\cdot\overline{z}_3}{\overline{z}_1\cdot \overline{z}_2\cdot\overline{z}_3}.$$ $\endgroup$ – Daniel Fischer May 19 '15 at 21:10
  • $\begingroup$ generally also newton's identities come in hand (en.wikipedia.org/wiki/Newton%27s_identities) $\endgroup$ – Ant May 19 '15 at 21:11

Since $|z_i|=1\iff z_i\overline{z_i}=1$, one has$$\begin{align}\overline{\left(\frac{z_1+z_2+z_3+z_1z_2+z_2z_3+z_3z_1}{1+z_1z_2z_3}\right)}&=\frac{\overline{z_1+z_2+z_3+z_1z_2+z_2z_3+z_3z_1}}{\overline{1+z_1z_2z_3}}\\&=\frac{\overline{z_1}+\overline{z_2}+\overline{z_3}+\overline{z_1z_2}+\overline{z_2z_3}+\overline{z_3z_1}}{1+\overline{z_1z_2z_3}}\\&=\frac{\frac{1}{z_1}+\frac{1}{z_2}+\frac{1}{z_3}+\frac{1}{z_1z_2}+\frac{1}{z_2z_3}+\frac{1}{z_3z_1}}{1+\frac{1}{z_1z_2z_3}}\\&=\frac{z_2z_3+z_3z_1+z_1z_2+z_3+z_1+z_2}{z_1z_2z_3+1}\\&=\frac{z_1+z_2+z_3+z_1z_2+z_2z_3+z_3z_1}{1+z_1z_2z_3}\end{align}$$

  • 7
    $\begingroup$ The heart of it is: 1) to show that something is real, show that it equals its own conjugate, and 2) for numbers on the unit circle, the conjugate is the same as the inverse. $\endgroup$ – Jack M May 20 '15 at 8:50
  • $\begingroup$ See my answer for a way to understand the innate reciprocation symmetry implicit in the above. $\endgroup$ – Bill Dubuque May 20 '15 at 15:48

By $\,z_i \bar z_i = 1,\,$ $\ {z\!+\!1}\,=\,\frac{(1+z_1)(1+z_2)(1+z_3)}{1+z_1z_2z_3}\, =\, \frac{z_1z_2z_3}{z_1z_2z_3}\frac{(\bar z_1+1)(\bar z_2+1)(\bar z_3+1)}{\bar z_1\bar z_2\bar z_3+\,1} = \overline{z\!+\!1},\,$ so $\ z = \bar z $

Remark $\ $ The innate symmetry can be seen nicely by polynomial reciprocation (reversal). Consider the (Vieta) generating function of the elementary symmetric functions $\,e_i$ of the $\,z_i$

$$ g(x,z_i)\, =\, (x-z_1)\cdots (x-z_n)\, =\, x^n - e_1 x^{n-1} + e_2 x^{n-2} -\cdots + (-1)^n e_n $$

Conjugation has the effect of reciprocating the $\,z_i,\,$ i.e $\,z_i\to \color{#c0f}{z_i^{-1}}.\,$ The effect of this on each factor $\,x - z_i\,$ is closely related to reciprocating $\,x,\,$ i.e. $\,x\to \color{#0a0}{x^{-1}},\,$ namely

$$\begin{align} z_i (x-\color{#c0f}{z_i^{-1}})\, & =\,z_i x - 1\, =\, -x\,(\color{#0a0}{x^{-1}}-z_i)\\ z_if(x,\,\color{#c0f}{z_i^{-1}})\, &=\, z_ix-1 \, =\, - xf(\color{#0a0}{\color{#0a0}{x^{-1}}},\,z_i)\end{align} $$

Applied to each linear factor $\,f\,$ in $\,g\,$ this yields

$$ z_1\!\cdots z_n\, g(x, \color{#c0f}{z_i^{-1}})\ =\ (-x)^n g(\color{#0a0}{x^{-1}}, z_i)$$

The RHS is up to sign the reciprocal polynomial of $\,g(x),\,$ i.e. that obtained by reversing the order of its coefficients. Comparing their coefficients of $\,x^k$ we get a $\,\rm\color{#c00}{{reflection}}\,$ formula

$$ \color{#c00}{e_{\large n}\,\overline{e_{\large k}}}\, =\, e_{\large n}\, e_{\large k}(z_i^{-1})\, =\,\color{#c00}{e_{\large n-k}} \quad $$

$${\rm e.g.}\quad \color{#c00}{e_3 \bar e_1 } \, =\, z_1 z_2 z_3 \left[\frac{1}{z_1} + \frac{1}{z_2}+\frac{1}{z_3}\right]\, =\, z_2z_3 + z_3 z_1 + z_1z_2\, =\, \color{#c00}{e_2}$$

Such reflections are evident in the calculations in mathlove's answer, viz.

$$\bar z\, =\, \frac{\bar e_1+\bar e_2}{\bar e_0+\bar e_3}\, =\, \frac{e_3}{e_3}\,\frac{\bar e_1+\bar e_2}{\bar e_0+\bar e_3}\, =\, \frac{\color{#c00}{ e_3 \bar e_1}+ e_3 \bar e_2}{e_3\bar e_0 + e_3\bar e_3}\, =\, \frac{\color{#c00}{e_2} +e_1}{e_3+e_0}\, =\, z$$

As always: $ $ exploit innate symmetry!


First, note that if $|z|=1$, then $z=\cos\theta+i\sin\theta$ for some $\theta$ and $1+z=1+\cos\theta+i\sin\theta=2\cos\frac{\theta}{2}e^{\frac{i\theta}{2}}$. Adding 1 to the original expression in the question, we have \begin{align*} \frac{(1+z_1)(1+z_2)(1+z_3)}{1+z_1z_2z_3}&=\frac{8\cos^2\frac{\theta_1}{2}\cos^2\frac{\theta_2}{2}\cos^2\frac{\theta_3}{2}e^{\frac{i(\theta_1+\theta_2+\theta_3)}{2}}}{2\cos^2\frac{\theta_1+\theta_2+\theta_3}{2}e^{\frac{i(\theta_1+\theta_2+\theta_3)}{2}}}\\ &=\frac{4\cos^2\frac{\theta_1}{2}\cos\frac{\theta_2}{2}\cos^2\frac{\theta_3}{2}}{\cos^2\frac{\theta_1+\theta_2+\theta_3}{2}} \end{align*} which is obviously real.


Hint: Add $1$ to the fraction (which doesn't affect its "reality") to get

$$ \frac{(1+z_1)(1+z_2)(1+z_3)}{1+z_1z_2z_3} $$

ETA: Apparently, I should make this more explicit.

For any $z$ such that $|z| = 1, \arg z = 2 \arg (1+z) \pm \pi$. We can see this by plotting the set $\{1+z: |z| = 1\}$ on the complex plane; it is a circle of radius $1$ with its center at $z = 1$. Given any point $1+z$, $\arg (1+z)$ is the angle between the real axis and a line from $0$ to $1+z$; $\arg z$ is the angle between the real axis and a line from $1$ to $1+z$. Since $0$ lies on the circle's circumference, and $1$ lies at its center, those angles are related by a ratio of $2:1$, and $\arg z = 2 \arg (1+z) \pm \pi$, where the $\pm \pi$ will not affect our "reality" argument below.

It can then be seen that both numerator and denominator have argument equal to $\frac{\arg z_1+\arg z_2+\arg z_3}{2} + k\pi$ (possibly with different values of $k$), so that the argument of the overall fraction is $0$ or $\pi$, and therefore the fraction (and the original expression) is real.


If $|z|=1$, then $z+\frac1z=z+\bar{z}=2\mathrm{Re}(z)$. Therefore, the following are both real: $$ \begin{align} \small\left(z_1+\frac1{z_1}\right)\left(z_2+\frac1{z_2}\right)\left(z_3+\frac1{z_3}\right) &\small=\frac{z_1^2z_2^2z_3^2+z_1^2z_2^2+z_2^2z_3^2+z_3^2z_1^2+z_1^2+z_2^2+z_3^2+1}{z_1z_2z_3}\tag{1}\\ z_1z_2z_3+\frac1{z_1z_2z_3} &=\frac{z_1^2z_2^2z_3^2+1}{z_1z_2z_3}\tag{2} \end{align} $$ The difference of $(1)$ and $(2)$ is also real: $$ \frac{z_1^2z_2^2+z_2^2z_3^2+z_3^2z_1^2+z_1^2+z_2^2+z_3^2}{z_1z_2z_3}\tag{3} $$ The ratio of $(3)$ and $(2)$ is also real: $$ \frac{z_1^2z_2^2+z_2^2z_3^2+z_3^2z_1^2+z_1^2+z_2^2+z_3^2}{z_1^2z_2^2z_3^2+1}\tag{4} $$ For any $w_1$, $w_2$, and $w_3$ whose absolute values are $1$, we can find $z_1$, $z_2$, and $z_3$ whose absolute values are $1$ so that $w_1=z_1^2$, $w_2=z_2^2$, and $w_3=z_3^2$. Plugging into $(4)$, we get that for any $w_1$, $w_2$, and $w_3$ whose absolute values are $1$, the following is real: $$ \frac{w_1+w_2+w_3+w_1w_2+w_2w_3+w_3w_1}{1+w_1w_2w_3}\tag{5} $$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.